Application of the Sanctions Method in Fostering Student Discipline - Megawati Abbas; Aryandi Sudika (International Journal on Advanced Science, Education, and Religion, 2022)
This paper examines the application of sanctions methods in fostering student discipline. The results showed that discipline is an exercise of character and mind for all actions of a person in accordance with existing regulations. The child discipline is basically a means of controlling, controlling, supervising and guiding against the child's behavior to achieve a better and effective action, and in accordance with the rules that have been approved or accepted as a form of responsibility. While punishment is something that is prescribed and is one of the successful means of education, which may occasionally be required by educators. But there is a very excessive use of this means, so that the facility is dangerous and has the opposite effect. The teacher in giving punishment should be wise with affection and tenderness. If conditions require a punishment, may apply it on condition not because of anger. Moreover, it does not apply punishment except on urgent conditions or is indispensable mainly due to discipline enforcement.